BASIC BELIEFS AND THE PERCEPTUAL LEARNING PROBLEM: A SUBSTANTIAL CHALLENGE FOR MODERATE FOUNDATIONALISM. - Lackey, Jennifer; Vaassen, Bram M. K. (Episteme (Cambridge University Press), 2016)
In recent epistemology many philosophers have adhered to a moderate foundationalism according to which some beliefs do not depend on other beliefs for their justification. Reliance on such ‘basic beliefs’ pervades both internalist and externalist theories of justification. In this article I argue that the phenomenon of perceptual learning – the fact that certain ‘expert’ observers are able to form more justified basic beliefs than novice observers – constitutes a challenge for moderate foundationalists. In order to accommodate perceptual learning cases, the moderate foundationalist will have to characterize the ‘expertise’ of the expert observer in such a way that it cannot be had by novice observers and that it bestows justification on expert basic beliefs independently of any other justification had by the expert. I will argue that the accounts of expert basic beliefs currently present in the literature fail to meet this challenge, as they either result in a too liberal ascription of justification or fail to draw a clear distinction between expert basic beliefs and other spontaneously formed beliefs. Nevertheless, some guidelines for a future solution will be provided.